Towards a theory for Enterprise Architecture (EA): a South African study - Coetsee, Rudolf (Department of Information Systems, 2024)
This paper describes a research exercise aimed at developing a theory that would describe the phenomenon of the use of Enterprise Architecture (EA) within South African organisations. The Strauss and Corbin (1998) grounded theory method was used, augmented by some principles taken from hierarchy theory. Data were collected by conducting semi-structured interviews with senior EA professionals. A total of 7 interviews were conducted Respondents from four organisations participated in this study. The organisations varied in size and industry sector, while the respondents varied in seniority and position. The theory that emerged consists of seven high-level concepts (i.e. "EA Department", "EA Role", ''EA Blueprint", "Business", "Information Technology (lT)", "Organisation" and "Environment''). In addition to these concepts, the theory also describes their characteristics and the relationships between them. The primary concept that emerged was "EA Department". Contrary to expectations from existing literature, the industry EA frameworks played an insignificant role in the emerging theory, whilst issues such as governance, selling the benefits of EA and the standing of the EA department within the organisation were more prominent. Another strong concept that emerged was "EA Blueprint". One of the characteristics of the "EA Blueprint" concept was the degree of enterprise coverage or scope. This characteristic emerged as the most important within the theory and therefore represents a strong sentiment that a more comprehensive enterprise model is a key factor in realizing EA benefits. Other findings that emerged from this study are that relationships between concepts within the theory do not exist in isolation Rather, they connect together to form what is termed "long chains of influence" in this paper. At least one recursive relationship or "spiral; was discovered in the data. This, together with the long chains of influence, exhibit certain properties similar to those found in chaos and complexity theory. This suggests that future research may benefit by using these theoretical lenses when attempting further description of the EA phenomenon The findings in this study are useful to future researchers as they introduce theory where very little exists in the field and may therefore act as a framework that may be used to describe and discuss the EA phenomenon in a structured manner. The theory is also valuable to practitioners wishing to enhance their EA practices.